Articulate Studio for Teaching and Learning Language - Asef Wildan Munfadlila; Deni Mustopa Mustopa; Ismail Suardi Wekke (IAIN PAREPARE, 2019)
The development of educational technology produces various educational concepts and practices that utilize media as a learning resource. Efforts to improve the quality of education have a variety of ways and in various components of education. To realize functions and achieve educational goals, improving the quality of learning in class is an important thing. The use of Articulate Studio in language teaching and learning is one of various ways as an alternative medium in the development of educational technology. Language classes only have activities once or twice a month that make students feel unable and the textbooks used there only provide limited practice for listening. To help teachers not only read listening scripts from books and use LCD, Audio, and Computer Laboratories available at school.